Rebuilding The Elite: A Case Study On Collaborative Injury Rehabilitation In Division 1 Sports - Hema, Poramet; Pirimova, Nargiza; Hossain, Md. Enayet (Multidisciplinary Journal of Tourism, Hospitality, Sport and Physical Education, 2025)
Purpose of the study: This study aims to explore the impact and effectiveness of a multidisciplinary approach in the injury rehabilitation of a Division 1 college athlete by combining medical, psychological, and performance perspectives. Methodology: This study used a qualitative case study method involving interviews, observations, and document analysis. A multidisciplinary team, including a medical doctor, psychologist, and athletic trainer, collaborated using performance tracking tools and recovery protocols to support the athlete’s rehabilitation. Main Findings: The rehabilitation approach led to a faster and more holistic recovery, improved the athlete’s psychological well-being, enhanced communication among professionals, and ensured return-to-play readiness. The collaborative model highlighted the importance of shared decision-making and athlete-centered care in optimizing injury rehabilitation outcomes. Novelty/Originality of this study: This study presents an integrative model for injury rehabilitation that emphasizes team-based care in collegiate sports. It offers new insights into the collaborative dynamics and structured communication among health professionals, advancing knowledge on how holistic approaches can be implemented effectively in high-performance athletic environments.